Maintenance Techniques for 3 Phase Induction Motors with a Voltage of 380 V on Air Fan Seals at PT Indonesia Power Suralaya - Nugraha, Adi; Pratiwi, Dini Austia (Universitas Nusa Putra, 2024)
PT PLN Indonesia Power Suralaya is a company engaged in power generation with a total capacity of 3400 MW, using coal as fuel. An air fan seal motor is a motor located in the burning of coal in a grinding tool commonly called a pulverizer. The air fan seal is an important motor that functions to protect the mill part from contamination of crushed coal powder. The air fan seal also helps keep the coal from entering the coal grinder inside the Pulverizer/Mill. The purpose of this study is to find out the techniques of PT Indonesia Power Suralaya in maintaining the performance of air fan seals so that coal-fired power plants can operate optimally. This research was carried out directly based on work experience in the work area of PT. Indonesia Power Suralaya PGU units 5-7. The results of this research consist of a combination of various actions used for the purpose of maintaining the company's assets. Maintenance can repair disruptions that occur until the asset is running according to its performance